Sensory and motor deficits - Malamos, Dimitris (Henry Stewart Talks, 2017)
Senses, Receptors-cranial nerves-brain sensory centers, Deficits causes and associated factors, Complications, Tests and recommended investigations, Treatment, Facial Nerve Paralysis, Upper and lower motor facial neuron paralysis